(untitled) (Research, Society and Development, 2020)
Among the various factors that influence the effectiveness of endodontic treatment, the filling material plays an important role. The aim of the present study was to evaluate the effectiveness of bioceramic cements and their applicability in endodontics. An integrative literature review of the literature was carried out in order to synthesize the knowledge pertaining to the theme. The research was carried out in the databases of Pubmed Medicine and CAPES Periodicals between the years 2015 and 2020, having as descriptors: “Biocompatible Materials”, “Endodontics” and “Silicate Cement”. Thirty-four scientific productions that met the inclusion criteria and were selected. The use of new bioceramic cements has shown a broad clinical applicability, in addition to having excellent properties, such as: ability to bond to dentin, good radiopacity, better handling conditions, appropriate setting time, bactericidal activity and bioactivity; moreover, they did not cause stains on the dental structures. However, the permanence of some deficiencies, such as the total removal of cement in the root canal and the high cost, points to the need for more research that explores the physical and chemical properties of these materials in the long term, in order to stimulate the making constant improvements in their compositions and making it possible to overcome the remaining deficiencies.